Varying Architecture of Heat Shock Elements Contributes to Distinct Magnitudes of Target Gene Expression and Diverged Biological Pathways in Heat Stress Response of Bread Wheat - Zhao, Peng; Javed, Sidra; Shi, Xue; Wu, Bingjin; Zhang, Dongzhi; Xu, Shengbao; Wang, Xiaoming (Frontiers in Genetics, 2020)
Heat shock transcription factor (HSF) bind to the cis-regulatory motifs, known as heat shock elements (HSEs), to mediates the transcriptional response of HSF target genes. However, the HSF-HSEs interaction has not been clearly understood. Using the newly released genome reference sequence of bread wheat, we identified 39,478 HSEs, 95.6% of which was non-canonical HSEs, and collapsed them into 30,604 wheat genes, accounting for 27.6% wheat genes. Using the intensively heat-responsive transcriptomes of wheat, we showed that canonical HSEs had a higher proportion to induce the response of closest downstream genes than non-canonical HSEs. However, the response magnitude induced by non-canonical HSEs was comparable with that induced by canonical HSEs. Significantly, some non-canonical HSEs which contain mismatched nucleotides at specific position within HSEs had larger response magnitude than canonical HSEs. Consistently, most of the HSEs identified in the promoter regions of heat shock protein encoding genes were non-canonical HSEs, suggesting an important role of non-canonical HSEs. Lastly, distinctly diverged biological processes were observed between genes containing different types of HSEs, proposing sequence variation of HSEs played key roles in the evolution of heat response and adaptation. Our results provided a new perspective to understand the regulatory network underlying heat response.